The hyperbola 6x² - 5y² + 12x + 50y - 149 = 0 represented in standard form is (x + 1)²/5 - (y - 5)²/6 = 1
Converting the hyperbola equation to standard form
From the question, we have the following parameters that can be used in our computation:
6x² - 5y² + 12x + 50y - 149 = 0
Rewrite as
6x² - 5y² + 12x + 50y = 149
Group the equation by the variables
6x² + 12x - 5y² + 50y = 149
So, we have
6(x² + 2x) - 5(y² - 10y) = 149
Complete the square on x and y
So, we have
6(x + 1)² - 5(y - 5)² = 149 + 6 - 125
This gives
6(x + 1)² - 5(y - 5)² = 30
Next, we divide through by 30
(x + 1)²/5 - (y - 5)²/6 = 1
Hence, the standard form is (x + 1)²/5 - (y - 5)²/6 = 1